Characterization of Caatinga vegetation and diet of steers in the "Sertão" of Pernambuco, Brazil - Moreira, José Nilton; Lira, Mário de Andrade; dos Santos, Mércia Virginia Ferreira; Ferreira, Marcelo de Andrade; Araújo, Gherman Garcia Leal de; Ferreira, Rinaldo Luiz Caraciolo; da Silva, Grécia Cavalcanti (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the botanical composition, the availability and quality of the fodder and diet of fistulated animals fed in an area of Caatinga, during the rainy season, in Pernambuco State, Brazil. Evaluations of botanical composition and fodder availability of herbaceous, arbustive and arboreous extracts were made in March and June. Fodder quality evaluation was performed through chemical analysis during the wet period. Sixty-seven species were found: 28 herbaceous, 20 arbustive and 18 arboreal; from these species, 19 were found in the animals diet. The fitomass availability from the herbaceous component varied from 1,369 kg ha-1 of dry matter (DM) in March, to 452 kg ha-1 of DM in June. The availability of the arbustive extract layer was close to the herbaceous, while the arboreal component contributed with only 178 kg ha-1 of DM. Despite the relatively high fitomass availability, only a small percentage was considered as fodder from the material found. It was observed a low digestion of the protein, probably due to high levels of lignin.